2023
DOI: 10.1007/s10238-023-01081-6
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-62/lymphocyte as a proposed predictive index for COVID-19 patients treated with monoclonal antibodies

Abstract: In a convenience sample of 93 patients treated with monoclonal antibodies (moAbs) against SARS-CoV-2, the interleukin-62/lymphocyte count ratio (IL-62/LC) was able to predict clinical worsening both in early stages of COVID-19 and in oxygen-requiring patients. Moreover, we analysed 18 most at-risk patients with asymptomatic or mild disease treated with both moAbs and antiviral treatment and found that only 2 had clinical progression, while patients with a similar risk were reported to have an unfavourable outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…A retrospective study of patients treated with monoclonal antibodies suggested that the IL6/lymphocyte count ratio is a valuable monitor to identify patients who need more treatment and support both in earlier and later stages of the disease. 22 …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of patients treated with monoclonal antibodies suggested that the IL6/lymphocyte count ratio is a valuable monitor to identify patients who need more treatment and support both in earlier and later stages of the disease. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, not only geographical differences reflecting heterogenicity in demographic and clinical characteristics of patients (5), but also the pandemic waves are an important factor which may have an impact on patient prognosis. For these reasons, prognostic scores (including clinical variables, radiological features and biomarkers) that were elaborated in the previous waves (35)(36)(37)(38)(39)(40) may change their accuracy across different pandemic waves and should be re-evaluated in the current epidemiological scenario.…”
Section: Figurementioning
confidence: 99%